El actual viejo debate de apertura y crecimiento - Ignacio Gómez Roldán (Suma de Negocios, 2013)
In Economics there is the debate on free trade and protection, considering arguments in favor of each of the positions. Currently, in times of the internationalization and globalization world, this debate has bringing together the approaches and experiences of several countries that have defined their trade and industrial policy for growth. Objective: To present and analyze theoretical arguments of the different positions and opposite to evidences of the countries on having adopted their policies. Methodology: As review document, it is based on existing literature for the construction of a structure that will lead to the analysis of the reality. Findings: It is difficult to find homogeneous measures of openness to the countries that allow to do comparisons. The trade policies are included in other type of policies and isolate the phenomenon of their effect on the growth of production is virtually impossible. The openings of the countries have happened in different moments of the time and the relating to the moment and structural international conditions of these environments also have changed. The effect of more experiences from different countries is relative and it is risky to draw valid conclusions for all countries different methodologies and econometric treatments.